Analisis Literasi Digital Siswa Kelas X Mata Pelajaran Dasar-dasar Kuliner di SMKN 9 Padang - Aldinda, Anggun; Siregar, Juliana (Lembaga Yasin AlSys, 2024)
Digital literacy in culinary lessons for class X students at SMKN 9 Padang is still not optimal. This can be seen from the learning results of students in the Culinary Basics lesson in class X, many of whom have not yet reached the KKM. This research aims to analyze digital literacy in Class X Culinary Basics lessons at SMK Negeri 9 Padang. This type of research is quantitative. The population of this study was all class X students at SMKN 9 Padang totaling 210 people. Sampling in the study used the Slovin formula so that a sample of 138 was obtained using the proportional random sampling technique. The data collection instrument uses a questionnaire using a Likert Scale, data analysis techniques include descriptive. The results of the research found that digital literacy in culinary basics subjects at SMKN 9 Padang was considered good. If we look at each of the internet search indicators, hupertect directions, evaluation of information content and knowledge compiler, they are in the good category.